Correction to: Swedish translation and validation of the Pediatric Insomnia Severity Index - Charlotte Angelhoff; Peter Johansson; Erland Svensson; Anna Lena Sundell (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.